Postawy i bariery w planowaniu inwestycji na przykładzie gmin województwa lubelskiego - Myna, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper presents the findings of an analysis of attitudes and barriers of investment planning, as exemplified by the poorly urbanised municipalities of the Lublin voivodship. The treasurers of 37 gminas were interviewed face to face about formulating the investment plans. The results of the study indicate that investment plans of the municipalities usually cover a one-year term. Such an attitude is enhanced by the awareness of overcoming elementary barriers to local development in the conditions of a permanent lack of funds in municipalities and the increasing stress of current tasks. Investment expenditure planning is impeded by the uncertainty - permanent changes of law, low predictability and difficulties with the implementation of communal revenue. Barriers to projecting of investment medium-range plans are created by the inability to prepare them, which is connected with low political culture and education of clerks in some of the municipalities. Faced with barriers in planning of investment, some rural municipalities and small towns of Lublin region will most probably not be able to use Structural Funds and Cohesion Fund. In this way they would forfeit the prospective benefits of the integration with the European Union. As a result, regional social-economic development disparities would deep. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 261-268